2003
DOI: 10.1088/0953-8984/15/21/101
|View full text |Cite
|
Sign up to set email alerts
|

Orthorhombic strontium titanate in BaTiO3–SrTiO3superlattices

Abstract: It has been suggested by several authors that SrTiO 3 layers in SrTiO 3 -BaTiO 3 superlattices should be tetragonal and ferroelectric at ambient temperatures, like the BaTiO 3 layers, rather than cubic, as in bulk SrTiO 3 , and that freeenergy minimization requires continuity of the polarization direction. A recent ab initio calculation constrained solutions to this structure. Surprisingly, our x-ray study shows that the SrTiO 3 layers are orthorhombic with 0.03% in-plane strain, with the BaTiO 3 c-axis matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 17 publications
4
48
1
Order By: Relevance
“…In addition to the dielectric permittivity change and strain relaxation, one can also consider the possible crystallographic symmetry lowering that is also known to greatly influence the ferroelectric properties of ferroelectricparaelectric SLs. 33,34 However, we could not confirm such symmetry change in our SLs within the resolution of our in-house x-ray diffraction. It is also worthy to note that a recent first-principles study (Ref.…”
contrasting
confidence: 60%
“…In addition to the dielectric permittivity change and strain relaxation, one can also consider the possible crystallographic symmetry lowering that is also known to greatly influence the ferroelectric properties of ferroelectricparaelectric SLs. 33,34 However, we could not confirm such symmetry change in our SLs within the resolution of our in-house x-ray diffraction. It is also worthy to note that a recent first-principles study (Ref.…”
contrasting
confidence: 60%
“…As an example, this analysis has proved useful in the interpretation of first-principles results and experiments on the structure of partiallyrelaxed SrTiO 3 /BaTiO 3 superlattices. 26,27 First-principles information about the effects of epitaxial strain on the structure and polarization of component layers also allows us to determine the relative stability of a given superlattice. It is well known that lattice matching of the components minimizes the elastic energy and thus increases the stability.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the relaxed ST/BT superlattices may possess symmetries lower than tetragonal. 6,7,10,11,14 However, the tetragonal symmetry in the BT layer is still retained with the polarization along the out-of-plane direction. It should be noted that the BT layers are still under an in-plane compressive strain even though the superlattice is fully relaxed with respective to the ST substrate.…”
Section: ͑1͒mentioning
confidence: 99%